2022
DOI: 10.3390/ijerph191710916
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Laboratory, and Imaging Findings of Pregnant Women with Possible Vertical Transmission of SARS-CoV-2—Case Series

Abstract: The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) pandemic significantly impacted the general population’s health. At times, the infection has unfavorably influenced pregnancy evolution and the result of birth. However, vertical transmission of the virus is rare and generates controversial discussions. The study aimed to highlight the clinical, laboratory, and imaging findings of pregnant women with confirmed Coronavirus Disease 2019 (COVID-19) with possible vertical transmission and identify po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Low levels of iron have been reported in Romanian patients early on, accordingly to international data [ 56 , 72 , 88 ]; however, there have been cases of normal values reported [ 54 , 86 , 89 , 90 ], while others have reported high levels of FER, including in children [ 14 , 21 , 23 , 24 , 25 , 26 , 29 , 30 , 31 , 35 , 36 , 41 , 43 , 48 , 62 , 74 , 79 ], with a few rare cases of vertical transmission describing increased FER levels, as observed in Iacob et al’s study [ 64 ].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…Low levels of iron have been reported in Romanian patients early on, accordingly to international data [ 56 , 72 , 88 ]; however, there have been cases of normal values reported [ 54 , 86 , 89 , 90 ], while others have reported high levels of FER, including in children [ 14 , 21 , 23 , 24 , 25 , 26 , 29 , 30 , 31 , 35 , 36 , 41 , 43 , 48 , 62 , 74 , 79 ], with a few rare cases of vertical transmission describing increased FER levels, as observed in Iacob et al’s study [ 64 ].…”
Section: Resultsmentioning
confidence: 96%
“…An increase in LDH activity was seen in many cases of severe COVID-19, which may be related to cell destruction as well as poor blood flow and oxygen delivery. Elevated LDH levels were observed in many studies of Romanian patients [ 21 , 26 , 33 , 34 , 79 ], with one study focusing on how these values could be related to thrombotic microangiopathy by presenting a case report of a patient with a complement gene variant (complement factor I) [ 80 ] and another focusing on a pediatric case, signaling the risk for a systemic inflammatory syndrome associated with COVID-19 in some children [ 23 ]. Neonatal vertical infection is rare; however, in those cases, LDH was elevated [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite evidence of placental histology and newborn immunological blood tests, the rate of reported congenital COVID-19 infection is very low, ranging from 3.2% to 8.40% [ 11 , 47 , 48 ]. In a previous study, our team also reported cases of possible vertical transmission [ 49 ]. When the newborns experience COVID-19 symptoms, they are likely to require respiratory support or to be transferred to a neonatal ICU, particularly if their mothers are symptomatic, too [ 50 ].…”
Section: Discussionmentioning
confidence: 99%